Koi sleepy disease (KSD) - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2017)
Carp edema virus (CEV) is a poxvirus, which is classified in family Chordopoxvirinae. CEV causes a serious health impact on juvenile carp. In some several countries of Asia, Japan for instant, CEV was commonly detected in several fish farms. This is consistent with the epidemiological data in Europe such as in England, Netherland, Austria and Germany respectively. Affected fish show lethargic movement, enopthalamia, swollen and necrotic gill, which induced anoxia and subsequently cause death, which more than 80 % mortality rate was found. Detection of CEV in sickness fish with PCR and nested PCR showed low sensitivity of detection. Therefore, real-time PCR was developed for detection of CEV. This method has more sensitivity response and could detect viral load in sample.